Understanding and guiding technology use in dementia: a pan-European mapping and consensus study - Tsabary, Canaan; Sezgin, Duygu; Innes, Anthea; Gove, Dianne; Diaz, Ana; Fernandes, Lia; Barbosa, Ana; Craven, Michael P.; Vollmar, Horst Christian; Øksnebjerg, Laila; Hopper, Louise (Frontiers in Dementia, 2025)
IntroductionDementia is a leading cause of disability worldwide, and its prevalence is expected to rise significantly by the year 2050. Assistive technologies (AT) have emerged as promising tools to promote independence and quality of life. The COVID-19 pandemic prompted an increased uptake of AT among people with dementia, exposing important limitations in digital literacy, accessibility, and support.MethodsThis pan-European study mapped recent research initiatives involving digital technology use by people with dementia during the pandemic and synthesised a set of recommendations for supporting the use of AT by people with dementia, and its development, using the Delphi method.ResultsThe mapping exercise identified 28 relevant projects, highlighting the types of technologies used during the pandemic and the settings in which they were implemented. Video-conferencing platforms were the most reported projects. More than half of the projects and initiatives (n = 17) were adapted to include digital technologies due to the pandemic. The subsequent Delphi consensus study incorporated input from experts by experience and produced 18 evidence-based recommendations, adapted from this mapping exercise and a previous scoping review.DiscussionKey findings emphasise involving people with dementia in technology design, ensuring equitable access, and providing adequate training and support. The recommendations offer a practical, consensus-based framework to improve the efficacy of AT adoption, with implications extending beyond pandemic contexts to improve dementia care globally.